2019
DOI: 10.1634/theoncologist.2018-0383
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Impacts Tumor Response Rate to Nivolumab in Patients with Advanced Malignancies

Abstract: Background. There has been a significant increase in the use of immunotherapy and cannabis recently, two modalities that have immunomodulatory effects and may have possible interaction. We evaluated the influence of cannabis use during immunotherapy treatment on response rate (RR), progressionfree survival (PFS), and overall survival (OS). Subjects, Materials, and Methods. In this retrospective, observational study, data were collected from the files of patients treated with nivolumab in the years 2015-2016 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
2
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(148 citation statements)
references
References 28 publications
3
126
2
3
Order By: Relevance
“…One third (31%) of the patients asked in our study, took medical cannabis believing that it will treat the cancer disease itself. It may be based on research showing that combinations of different compounds in cannabis can be extremely effective in destroying speci ic cancer cells [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One third (31%) of the patients asked in our study, took medical cannabis believing that it will treat the cancer disease itself. It may be based on research showing that combinations of different compounds in cannabis can be extremely effective in destroying speci ic cancer cells [4].…”
Section: Discussionmentioning
confidence: 99%
“…A new Israeli study supports the idea that cannabis could be used to kill cancer cells .Biologist Dr. David Meiri of the Technion-Israel Institute of Technology, is conducting cutting-edge research showing that combinations of different compounds in cannabis can be extremely effective in destroying speci ic cancer cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hindering therapeutic efficiency of human IgG4 monoclonal antibody Nivolumab is an unwanted action. Troubling results have been obtained in an oncologic study featuring the effectiveness of associating cannabis to the human IgG4 monoclonal antibody Nivolumab in the treatment of various cancers including melanoma, as cannabis decreased the response rate to the treatment, hinting at possible interactions between the therapeutic substances [205].…”
Section: Adverse Effects Of Cannabinoidsmentioning
confidence: 99%
“…There also are significant concerns regarding drug‐drug interactions with the use of medical cannabis . For example, in patients with cancer, one study found that cannabis was the only factor significantly associated with a decreased response rate to nivolumab immunotherapy, with a decrease in the response rate from 38% to 16% when patients were taking cannabis during immunotherapy . Another review recommended caution when combining cannabis with specific agents given the potential effects of cannabis on membrane transporters and cytochrome P450 metabolism .…”
Section: Cannabis: Indications Use Versus Evidence Basementioning
confidence: 99%